2017
DOI: 10.4049/jimmunol.1700140
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Impaired Filamentous Actin Polymerization Signaling Reduces Alveolar Macrophage Phagocytosis of Bacteria

Abstract: In elderly patients bacterial infection often causes severe complications and sepsis. Compared to younger patients, older patients are more susceptible to sepsis caused by respiratory infection. Macrophage (Mϕ) phagocytosis of bacteria plays a critical role in the clearance of pathogens and the initiation of immune responses. It has been suggested that Mϕ exhibit age related functional alterations, including reduced chemotaxis, phagocytosis, antibacterial defense, and ability to generate reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Furthermore, our results are in accordance with the report showing the age‐dependently elevated expression of MARCO on the surface of microglia . On the other hand, it was shown that there is no difference in the level of MARCO expression between young and aged alveolar Mф . Importantly, expression of MARCO was significantly up‐regulated in lipopolysaccharide‐induced tolerant Mф .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our results are in accordance with the report showing the age‐dependently elevated expression of MARCO on the surface of microglia . On the other hand, it was shown that there is no difference in the level of MARCO expression between young and aged alveolar Mф . Importantly, expression of MARCO was significantly up‐regulated in lipopolysaccharide‐induced tolerant Mф .…”
Section: Discussionsupporting
confidence: 92%
“…Further study is required to determine whether baseline elevations of the receptors we have identified as upregulated on MDMs from COPD subjects, are also increased in alveolar macrophages, though complement receptor 3 (CR3) and CR4 expression on AM have been shown to have higher baseline expression in subjects with COPD (both current and ex-smokers) as compared to non-smoker controls[35, 40, 41]. Whether these receptors will downregulate after bacterial challenge in alveolar macrophages, similarly to the MDMs, is also unknown, particularly for the key scavenger receptors SR-AI and MARCO, though reductions have been observed in murine models[42]. The current data on responses of bacterial recognition receptors on human alveolar macrophages to bacterial exposure in COPD is limited to a single study, where TLR2 and TLR4 increased expression after challenge with live Moraxella catarrhalis (MC), NTHI and SP in adherent alveolar macrophages[26].…”
Section: Discussionmentioning
confidence: 99%
“…This increased ROS production in ADMSCs from aged rats was attenuated by CASIN with no significant effects on CM-H2DCFDA intensity in younger cells. Impaired actin polymerization is another hallmark of cell senescence (Kasper et al 2009;Li et al 2017;Xu et al 2017), and it can be mediated by the upregulation and activation of Cdc42 (Tang and Gunst 2004;Zlotorynski 2015). We employed QIM of F-actin labeled with Actin-green TM 488 ReadyProbes TM cells to quantify actin polymerization in ADMSCs isolated from young and old animals.…”
Section: Admscs From Young and Aged Ratsmentioning
confidence: 99%